Agronomic behavior and nutritional quality of Tithonia diversifolia in a flooded savannah ecosystem in Casanare, Colombia (Revista Sistemas de Producción Agroecológicos, 2020)
The flooded savannah ecosystem in Paz de Ariporo, Casanare, Colombia is characterized by being an alluvial plain that lasts six to eight months flooded, where there is a great aquatic and terrestrial biodiversity, therefore, it is an environment conducive to the implantation of new forage species with good nutritional value for livestock production, such as buttercup or arnica (Tithonia diversifolia). The present study was carried out under the parameters of quantitative and experimental research, where a nursery was planted with 1000 stakes of arnica, to later cover an area of 1000 m2 with arnica at a planting density of 1 m x 1 m. In both stages, both in the nursery and in the field, data was collected on the following variables: germination percentage, survival percentage, number of days to first regrowth, plant height, nutritional analysis; in order to evaluate its behavior in a flooded savannah ecosystem. The results indicate a better agronomic behavior of the plant material with the addition of organic fertilizer in terms of the variables observed, however, in some cases the difference is not significant, although compared to other studies the buttercup is seen as an excellent alternative. fodder to feed cattle. The germination percentage was 92%, in the nursery and in the field, it was 97.5%; In addition, treatment one with CaO showed better behavior in terms of plant height, with plants reaching an average of 115 cm.
Keywords: shrubs; tropical zone; agronomic behavior